2010
DOI: 10.1891/1061-3749.18.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Huntington Disease Family Concerns and Strategies Survey From Focus Group Data

Abstract: Health concerns and management strategies among families of young and middle-age adults with Huntington’s disease (HD) are unknown. This study developed and tested psychometric properties of the Huntington Disease Family Concerns and Strategies Survey (HDFCSS). Focus group data from 91 adult family members were used to develop content. Content analysis yielded four domains that were transferred into Personal, Person With HD, Community Health Care Services, and Strategies scales. Focus group data, expert valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…The design of the larger study is reported in more detail elsewhere (Sparbel et al, 2008; Williams & Ayres, 2007; Williams et al, 2007; Williams et al, 2008). In brief, the larger study was a two phase mixed methods study in which the conduct of focus groups and development of a family concerns and strategies survey were completed in the first phase, and the survey was distributed and analyzed in the second phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the larger study is reported in more detail elsewhere (Sparbel et al, 2008; Williams & Ayres, 2007; Williams et al, 2007; Williams et al, 2008). In brief, the larger study was a two phase mixed methods study in which the conduct of focus groups and development of a family concerns and strategies survey were completed in the first phase, and the survey was distributed and analyzed in the second phase.…”
Section: Methodsmentioning
confidence: 99%
“…Groups extended from 1 to 2 hours, length did not appear to be related to the number of participants in the groups. Teen and adult participants were asked to describe concerns regarding themselves, concerns regarding the health of the family member with HD, strategies used to manage these concerns, and what could help them (Williams et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…However, no measures of family members' perception of health care services for persons with Huntington Disease were found. Thus, a new measure of Community Health Care Services (CHCS) for family of persons with HD was developed and fully described elsewhere 18. (unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…This instrument was developed from a larger parent study whose purpose was to identify concerns of family members of persons with HD and strategies used to manage these concerns 19. The parent study used a mixed methods design in which common themes were identified from focus groups with 91 adult family members at six sites in the US and Canada, and a survey was constructed from the themes and focus group statements 18. (unpubl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation